Physico-mechanical properties of Spanish juniper wood considering the effect of heartwood formation and the presence of defects and imperfections - Fuente León, Javier de la; Lafuente Jimenez, Edgar; Hermosilla, Dahpne; Broto Cartagena, Miguel; Gascó, Antonio (Ministerio de Educacion y Ciencia, 2014)
Aim of study: Determining the main physical and mechanical properties of Spanish juniper wood from Soria (Spain) considering the effects of heartwood formation and the presence of defects and imperfections; and comparing the resulting characteristics with similar existing data for other regional softwood species of commercial interest. Area of study: Berlanga de Duero (Soria,Castilla y León),Spain. Material and Methods: Wood physico-mechanical performance was determined by Spanish UNE standards in order to provide proper comparisons to other regional softwood species. An individual tree representing average plot characteristics was selected in all eight 10 m radius circular plots that were established well-representing the heterogeneity of this woodland. The age of every tree was determined reading the number of growth rings at the base of each sampled tree. Every physico-mechanical property was assessed at least 4 times for every wood sample type (sapwood and heartwood,whether clear or with the presence of defects) of each tree. Two-way ANOVA was run to assess significant differences in the results. Post hoc all pairwise comparisons were performed using Tukey's test (p < 0.05). Research highlights: Spanish juniper wood resulted harder than other regional commercial conifers,and showed semi-heavyweight heartwood and lightweight sapwood; whereas shrinkage figures remarked its great dimensional stability. The high presence of knots within heartwood made it even heavier,harder,and more resistant to compression parallel to grain. A commercial use of this rare precious wood may contribute to juniper forests preservation in the frame of forest sustainable management plans.
Keywords: ODS 13 - Acción por el clima; ODS 15 - Vida de ecosistemas terrestres